Exploratory Study on the Impact of Sukuk in the Nigerian Transportation Sector - Bilya, Bilyaminu Muhammad; Sani, Dr. Abubakar (International Journal of Islamic Economics and Governance, 2024)
Sukuk is an alternate financial instrument adopted in Nigeria by the enactment of financial acts to attract public-private partnerships (PPPs) for mutual investment to achieve infrastructural development. The study was conducted using a qualitative research method to establish the impact of the Nigerian sovereign Sukuk ventured over seven (7) years, where funds were generated to execute projects within the Nigerian transportation system by the rehabilitation of some dilapidated roads and construction of new projects to enhance transportation and achieve the sustainable flow of raw materials and finished goods in the country. The research identified challenges to the product’s application for its limited use at the federal level alone despite the existence of vast potencies in the state and local administrative transportation purview. The work recommends a massive awareness campaign to clear misconceptions that relinquished other religious followers and common people from the inception of the instrument in the economic domain of the country.